REPOSISI PERAN KARANG TARUNA DALAM TATA KELOLA DESA: DARI PELAKSANA KEGIATAN MENJADI PENGELOLA DATA BERBASIS KOMUNITAS - Astuti Astuti; Saenab Saenab; Aiman Sabar Rezeky (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Village youth organizations (Karang Taruna) have traditionally functioned as activity implementers in village governance, with limited participation in data management and evidence-based decision-making. This community service program aimed to reposition Karang Taruna members as community-based data managers by strengthening their statistical and digital literacy capacities. Using a participatory capacity-building approach with 25 Karang Taruna members in Barru Regency, South Sulawesi, the program integrated hands-on training in basic descriptive statistics and cloud-based digital tools. Evaluation results indicate that 80% of participants were able to calculate activity participation rates using spreadsheets, while 72% successfully designed digital survey instruments using Google Form. Analysis of organizational behavior change reveals a significant shift from passive program execution toward active data stewardship and evidence-based program evaluation. The findings demonstrate that integrating statistical and digital literacy within youth organizations substantially strengthens youth civic engagement, promotes community data empowerment, and positions Karang Taruna as strategic digital inclusion agents within the village governance ecosystem. This repositioning enables youth to bridge the technological gap in village administration, thereby contributing to more participatory, transparent, and accountable village governance from a bottom-up perspective. Keywords: community data empowerment; digital inclusion; Karang Taruna; village governance; youth civic engagement.